Lead-time optimization potential of digitization in air cargo - Benjamin Bierwirth; Kai-Oliver Schocke (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
The air cargo supply chain consists of several parties: the forwarders collect air cargo shipments and consolidate these shipments in regional warehouses all over the continent. They decide upon the export airport and bring it there to consolidate all shipments in their air cargo hub - warehouse according to the chosen flight. Using local truckers, the shipments, consolidated by airline, are forwarded to the handling agents to load air cargo containers or to build up air cargo pallets. The containers or pallets are brought to the apron and loaded into the planes. There is not a single chain existing; the parties involved are part of a dynamic n * m * o network which is fixed with every single shipment. The problem addressed in this paper is to document the waiting times at the level of the handling agents. Own, long time research at Frankfurt International Airport shows, that the waiting time for the trucker in front of handling agents warehouses significantly influence the lead-time for shipments. We identify the barriers to a faster adaption of digitization, which is currently around 30% in Frankfurt. Quantifying the impact of waiting times and required warehouse space due to long lead-times allows for a cost estimate.
urn:nbn:de:gbv:830-88217500; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; air cargo; lead-time reduction; digitization; air cargo supply chain